Knowledge Diplomacy: Findings, Misunderstandings, and Challenges - Knight, Jane (International Higher Education, 2023)
Knowledge diplomacy is a collaborative approach, based on values of reciprocity and mutual benefits, aimed at strengthening relations among countries through international higher education, research, and innovation. It is often confused with soft power and cultural, science, and public forms of diplomacy. This article clarifies similarities and differences among the different approaches and identifies current challenges.